MAFLD considerations as a part of the global hepatitis C elimination effort: an international perspective. Issue 10 (22nd March 2021) - Fouad, Yasser; Lazarus, Jeffrey V.; Negro, Francesco; Peck‐Radosavljevic, Markus; Sarin, Shiv K.; Ferenci, Peter; Esmat, Gamal; Ghazinian, Hasmik; Nakajima, Atsushi; Silva, Marcelo; Lee, Samuel; Colombo, Massimo
Summary: Background: The World Health Organization (WHO) set a goal to eliminate hepatitis C (HCV) infection globally by 2030, with specific targets to reduce new viral hepatitis infections by 80% and reduce related deaths by 65%. However, an overlooked aspect that may hinder these efforts is the impact other liver diseases could have by continuing to drive liver disease progression and offset the beneficial impact of DAAs on end‐stage liver disease and hepatocellular carcinoma (HCC). In particular, the decrease in HCV prevalence has been countered by a marked increase in the prevalence of metabolic‐associated fatty liver disease (MAFLD). Aims: To review the potential interaction of HCV and MAFLD. Methods: We have reviewed the literature relating to an arrange of interaction of HCV, metabolic dysfunction and MAFLD. Results: In this viewpoint, international experts suggest a holistic and multidisciplinary approach for the management of the growing number of treated HCV patients who achieved SVR, taking into consideration the overlooked impact of MAFLD for reducing morbidity and mortality in people who have had HCV. Conclusions: This will strengthen and improve the continuum of care cascade for patients with liver disease(s) and holds the potential to alleviate the cost burden of disease; and increase quality of life for patients following DAAs treatment.